Peculiarities of the use of CAT and DOG artistic concepts (on the material of fiction). - Сердюк, Ольга Вікторівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article deals with the peculiarities of the use of concepts with animalistic components cat and dog in fiction, that serve as carrier of specific cultural-historical space. Investigation is carried out with the help of verbalization analysis of CAT and DOG concepts in the works of world literature. Atention is paid to certain characteristic features of zoonym concepts. A conclusion is drawn about the necessity of further investigation of zoonym units, understanding and description of verbalization of the concept sphere with the animalistic elements cat and dog in literature.